Determinan Return On Asset Bank BRI Syariah Periode 2015-2019 - Ilani Pujiyanti; Faisal Rakhman (Jurnal Maps (Manajemen Perbankan Syariah), 2020)
The level of BRISyariah Capital Adequacy Ratio (CAR) for the period 2015-2019 is already in the very healthy category (above 12%), while the level of Financing to Deposit Ratio (FDR) is still in a fairly healthy category (around 85%), the ratio of Operating Costs to Operating Income ( BOPO) is in the unhealthy category (above 95%), as well as the level of Return On Assets (ROA), especially during 2019, is in the unhealthy category (below 0.5%). This study analyzes the influence of CAR, FDR, BOPO on ROA in BRISyariah. This research is a quantitative type with an associative approach. With secondary data in the form of published quarterly financial reports of BRISyariah for the period 2015-2019. Tests conducted to determine the relationship and influence between variables partially and simultaneously, multiple regression, coefficient of determination, t test and F test. The results of this study indicate that (1) there is a negative effect of CAR on ROA where the value of tcount>ttable (2.352>2.120) is on the negative side with R2 of 23.5%, (2) there is no effect of FDR on ROA where the tcount value is<ttable (-0,127<2,120) with R2 of 0.1%, (3) there is a negative effect of BOPO on ROA where the tcount>ttable (11,823>2,120) with the tcount on the negative side, while the R2 value is 88.8 %. (4) simultaneously there is a significant effect of CAR, FDR and BOPO on ROA with the results of Fcount>Ftable (331,743> 3,24) with a R2 value of 98.4%. The concluded that the risk of own capital (CAR) in high number and the more inefficient bank operations (BOPO), make ability the bank's is low to increase profits.